Urban Sprawl in Romania: The Case of Bucharest - Georgios Kapraras (Urbanism. Arhitectura. Constructii, 2024)
In this paper, the notions of urban sprawl and suburbanisation are introduced and discussed in the context of American and European cases. The drivers of urban sprawl are discussed along with the main typologies analysed in the literature about the issue. The debate regarding urban sprawl is discussed in the particular context of Eastern Europe, and a timeline of suburbanisation is presented from the socialist years until today. Then, the specific case of Bucharest is examined through the case of Popesti Leordeni, where the particularities of the city development and the stages of urban sprawl are compared with the typologies observed in the Romanian context. The paper concludes with the need for further research to identify different or diverging planning practices within the metropolitan area.